Talking to the Shameless?: Sexual Violence and Mediation in Intrastate Conflicts. (September 2019) - Nagel, Robert Ulrich
To what extent, does sexual violence influence the likelihood of conflict management in intrastate conflicts? Despite a growing body of research that explores conflict-related sexual violence, the literature presents little insight on its effects on conflict resolution. Extending feminist international relations (IR) theory to intrastate conflicts and applying a gender lens to the power to hurt argument, I argue that when rebel sexual violence is public knowledge, the likelihood of conflict management increases because the state perceives it as a threat to its masculinity. I systematically test this argument on all intrastate conflict years from 1990 to 2009 using the Sexual Violence in Armed Conflict and the Civil War Mediation data set. The results provide robust support for the argument. This presents an important refinement of traditional rationalist conflict bargaining theories and opens new avenues for the research and practice of conflict management.